Analysis of Scientific Approach Implementation in Biology Learning at Senior High School - ika anggraeni (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Curriculum 2013 is the development of curriculum KTSP. In this curriculum there were four competencies (KI) are KI-1 (religious attitudes), KI-2 (social attitudes), KI-3 (knowledge) and KI-4 (skill). KI-1 and KI-2 integrated in the KI-3 and KI-4. One of Learning approach in Curriculum 2013 is Scientific Approach with do activities like observing, questioning, experiment/ trying/exploration, processing and communicate information. The aim of the study is to observe Scientific Approach in the RPP and its appropriateness in learning. This is a descriptive study by using purposive sampling technique. The data obtained through the study of the documentation, observation, and interviews. The sample of the study is a Cluster III’s Senior High School that piloting by Curriculum 2013 at Bandung. The results of the study showed in generally, the content of Scientific Approach in the RPP is 69,17% and its appropriateness is 57,84%. This means that scientific approach in Biology learning has not been done well.